ADAMTS-13 in Critically Ill Patients With Septic Syndromes and Noninfectious Systemic Inflammatory Response Syndrome. Issue 6 (June 2015) - Aibar, Jesús; Castro, Pedro; Espinosa, Gerard; Fernández, Sara; Hernández, Cristina; Rinaudo, Mariano; Butjosa, Montserrat; Tàssies, Dolors; Reverter, Joan Carles; Nicolás, Josep Maria
<x xml:space="preserve">Abstract</x> ABSTRACT Purpose: Decreased ADAMTS-13 (A Disintegrin and Metalloprotease with a ThromboSpondin type 1 motif, member 13) seems to be associated with a poor prognosis in sepsis. However, its role in different septic syndromes and other causes of systemic inflammatory response syndrome (SIRS) remains unclear. The aims of this study were to assess ADAMTS-13 levels in patients with septic syndromes or noninfectious SIRS and to determine their association with morbidity and mortality. Methods: The study population consisted of 178 patients admitted to the medical intensive care unit presenting either septic syndromes or noninfectious SIRS. ADAMTS-13 levels were analyzed. Results: Patients with septic syndromes showed significantly lower levels of ADAMTS-13 compared with those with noninfectious SIRS (P = 0.014). Patients with severe sepsis or septic shock presented lower levels than those of patients with sepsis (P = 0.086). A significant negative correlation was found between ADAMTS-13 levels and delta Sequential Organ Failure Assessment and Acute Physiology and Chronic Health Evaluation II scores at admission in the septic patients. Patients who died had significantly lower levels of ADAMTS-13 compared with survivors, both in the whole population and among the septic patients (P = 0.002 and P = 0.009, respectively). Logistic regression analysis showed that decreased ADAMTS-13 levels were associated with an increased risk of in–intensive care unit mortality (odds ratio, 0.985; 95% confidence interval, 0.973–0.998; P = 0.023). Conclusions: Septic patients have lower levels of ADAMTS-13 than do patients with noninfectious SIRS. Levels of ADAMTS-13 are correlated with illness severity in patients with septic syndromes. ADAMTS-13 levels were associated with an increased risk of mortality in critically ill patients with SIRS especially those with septic syndromes.